Petroleum Conservation in Theory and Practice - McKie, James W.; McDonald, Stephen L. (Quarterly Journal of Economics, 1962)
The economic meaning of conservation, 99. — The maximum efficient rate and well spacing, 101. — State regulation, 110. — The intensive and the extensive margin, 118.